Comprehensive warm-up programme to prevent injuries in young female footballers: cluster randomised controlled trial. (9th December 2008) - Soligard, Torbjørn; Myklebust, Grethe; Steffen, Kathrin; Holme, Ingar; Silvers, Holly; Bizzini, Mario; Junge, Astrid; Dvorak, Jiri; Bahr, Roald; Andersen, Thor Einar
Abstract : Objective To examine the effect of a comprehensive warm-up programme designed to reduce the risk of injuries in female youth football. Design Cluster randomised controlled trial with clubs as the unit of randomisation. Setting 125 football clubs from the south, east, and middle of Norway (65 clusters in the intervention group; 60 in the control group) followed for one league season (eight months). Participants 1892 female players aged 13-17 (1055 players in the intervention group; 837 players in the control group). Intervention A comprehensive warm-up programme to improve strength, awareness, and neuromuscular control during static and dynamic movements. Main outcome measure Injuries to the lower extremity (foot, ankle, lower leg, knee, thigh, groin, and hip). Results During one season, 264 players had relevant injuries: 121 players in the intervention group and 143 in the control group (rate ratio 0.71, 95% confidence interval 0.49 to 1.03). In the intervention group there was a significantly lower risk of injuries overall (0.68, 0.48 to 0.98), overuse injuries (0.47, 0.26 to 0.85), and severe injuries (0.55, 0.36 to 0.83). Conclusion Though the primary outcome of reduction in lower extremity injury did not reach significance, the risk of severe injuries, overuse injuries, and injuries overall was reduced. This indicates that a structured warm-up programme can prevent injuries in young female football players. Trial registration ISRCTN10306290 .